Investigating the Effectiveness of Private Small Group Tutoring of English in Kazakhstan: Perceptions of Tutors and Students - Akimenko, Olessya (NUGSE Research in Education, 2(1), 2017)
The main focus of education studies has been on mainstream schools and institutions. However, the growing phenomenon of private tutoring has been largely overlooked by scholars. In Kazakhstan, numerous specialists offer private tutoring, and the tendency to supplement mainstream schooling continues to grow. The actual effectiveness of private tutoring, meanwhile, remains an open question. Since the study of English language is the most popular among the various subjects offered by tutors, this research studies the effectiveness of private tutoring of English and the way it can – or cannot – complement school education. This qualitative study explores the experiences of five private tutors and five privately tutored small groups of high-school students at private tutoring facilities in Astana, based on data obtained from semi-structured individual face-to-face and focus group interviews. The results of the study indicate that private tutoring is effective in enhancing students’ knowledge of English, as well as serves as a remedial purpose by helping students to form the knowledge required by mainstream schools. However, it should be noted that for other tutored subjects the situation may be different. Also, the results of the research may not be representative for the whole country due to the small size of the sample.
Keywords: shadow education; informal education; private tutoring; small group tutoring; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education